A New Immigrant Experience of Navigating Multiculturalism and Indigenous Content in Teacher Education - Marom, Lilach (Canadian Journal of Higher Education, 2017)
In this article, which is grounded in my own experiences, I discuss the responsibilities of new immigrant teacher educators when teaching courses related to diversity and multiculturalism in Canada. I highlight the complexities that underlie discourses of multiculturalism in teacher education, and the important role that new immigrant teacher educators have in locating themselves within the frame of settler colonialism in Canada. I argue that there is a need for genuine dialogue and critical reflexivity that encourage teacher educators and teacher candidates to locate themselves within a complex web of privileges and oppressions, and I explore possible new directions for teaching multiculturalism and Indigenous content in teacher education.